Evaluation of periapical changes following endodontic therapy: digital subtraction technique compared with computerized morphometric analysis - Carvalho, F. B. [UNESP]; Gonçalves, Marcelo [UNESP]; Guerreiro-Tanomaru, J. M. [UNESP]; Tanomaru-Filho, M. [UNESP] (British Inst Radiology, 2009)
Objectives: The aim of this study was to compare two methods for the evaluation of periapical lesion changes following endodontic therapy (digital subtraction technique and morphometric analysis) by outlining the radiolucent area.Methods: 13 human anterior teeth with pulp necrosis and chronic periapical lesions were used. Periapical radiographs were taken immediately after endodontic therapy (0) and then 2 months, 4 months and 6 months post treatment, using an intraoral radiographic film holder stabilized with impression material. The films were processed in a standard manner and the digitized images were submitted to digital subtraction using Adobe Photoshop 6.0. New bone formation or bone resorption areas were then measured. In the morphometric analysis, the periapical lesions were outlined using VixWin 2000 and the area (in square millimetres) was recorded. The obtained data were submitted to agreement analysis for comparison of the two techniques.Results: There was no correlation between the areas of radiographic changes detected by digital subtraction and periapical lesion outline (r=0.02-0.45). The new bone formation areas observed by digital subtraction presented higher values, with bone changes being especially evident in the 2 month follow-up radiographs, which suggests a higher sensitivity for this method.Conclusions: Both methods are suitable for the evaluation of periapical lesion changes, but the digital subtraction technique is more sensitive for detecting radiographic periapical changes. Dentomaxillofacial Radiology (2009) 38, 438-444. doi: 10.1259/dmfr/53304677
Keywords: radiography; periapical periodontitis; digital subtraction radiography